ANALISIS PENGARUH SERVICESCAPE, EXPERIENTIAL MARKETING DAN PERCEIVED VALUE TERHADAP REVISIT INTENTION MELALUI SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi Kasus di Obyek Wisata Golaga Purbalingga) - Masrokhah, Siti; Suciningtyas, Santi; Prasetyo, Arif Hadi (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2025)
This research entitle of “Analysis of the influence of Servicescape, Experiential Marketing, and Perceived Value to Revisit Intention with Satisfaction as an Intervening Variable” (Case Study at The Golaga Purbalingga Tourism Object). This research target is : To gain an understanding of the influence of the Servicescape, Experiential Marketing, and Perceived to Revisit Intention with Satisfaction as an Intervening Variable. To research it uses accidental sampling and purposive sampling as much 100 respondents. The analysis tool in this stuy uses the SPSS version 26.0 program. As for examination of at this research done with validity test, reliability test, classical assumptions test, multiple linear regression analysis, hypothesis test, and sobel test. The validity of each variable question item is valid and reliability results of each variabel question item is reliable. The classical assumption test declared to meet classical assumption. The multiple linear regression analysis at this research obtained by result b1 = 0,187 showing influence which are positive of Servicescape variable (X₁) to Revisit Intention variable (Y), b2 = 0,117 showing influence which are positive of Experiential Marketing variable (X₂) to Revisit Intention variable (Y), b3 = 0,055 showing influence which are positive of Perceived Value variable (X₃) to Revisit Intention variable (Y), b4 = 0,215 showing influence which are positive of Satisfaction variable (Z) to Revisit Intention variable (Y). The results of the research partially showed that the Servicescape variable (X₁) has a significant influence on the Revisit Intention variable (Y) with a value of (tcount 2,119 > ttable 1,984), the Experiential Marketing variable (X₂) has not a significant influence on the Revisit Intention variable (Y) with a value of (tcount 1,612 < ttable 1,984), the Perceived Value variable (X₃) has not a significant influence on the Revisit Intention (Y) variable with a value of (tcount 0,886 < ttable 1,984), and the Satisfaction variable (Z) has a significant influence on the Revisit Intention variable (Y) with a value of (tcount 3,986 > ttable 1,984). The results of the research sobel test Satisfaction variable (Z) mediate the relationship between Servicescape variable (X₁) to Revisit Intention variable (Y) with value (tcount 2,139 > ttable 1,984), Satisfaction variable (Z) mediate the relationship between Experiential Marketing variable (X₂) to Revisit Intention variable (Y) with value (tcount 2,208 > ttable 1,984), Satisfaction variable (Z) mediate the relationship between Perceived Value variable (X₃) to Revisit Intention variable (Y) with value (tcount 3,083 > ttable 1,984).